Preparation method of high SeS2 loaded Te modified SnS / biochar composite electrode

By modifying the SnS/biocarbon composite electrode as the carrier of SeS2, the serious shuttle effect of lithium-selenium S2 batteries under high current density was solved, and Li-Selenium-S2 batteries were achieved with high SeS2 load and high rate performance. -SeS2 battery.

CN119480937APending Publication Date: 2025-02-18XIAN AERONAUTICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411613236.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Lithium-sulfur batteries and lithium-selenium batteries Due to the poor conductivity of sulfur and the high cost of selenium, lithium-selenium S2 batteries have challenges in high capacity and fast charging, especially polysulfides and polyselenium compounds at high current density. The shuttle effect is serious.

Method used

Te is used to modify the SnS/biocarbon composite electrode as the carrier of SeS2, and the adsorption and conversion ability of polysulfide and polyselenide are improved through the porous structure of biocarbon and the modification of Te, reducing the shuttle effect and increasing the magnification of Li-SeS2 batteries. performance.

Benefits of technology

It achieves a high SeS2 load capacity, enhances the adsorption and conversion capabilities of polysulfides and polyselenides, reduces the lithium ion diffusion energy barrier, and significantly improves the rate performance of Li-SeS2 batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480937A_ABST
    Figure CN119480937A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high SeS2-loaded Te modified SnS / biochar composite electrode. The preparation method comprises the following steps: mixing a Piriporus bulgaricus material, a phellinus igniarius material and a cellular bacteria material; adding gluconic acid, hyaluronic acid and lactic acid; performing solvothermal reaction; adding the mixed solution, uniformly stirring, and carrying out microwave heating, ultraviolet radiation and ultrasonic oscillation treatment; carrying out heat treatment at the temperature of 550-850 DEG C; adding ethylene glycol and an alkyl tin compound, uniformly stirring, and carrying out hydrothermal reaction at 170-180 DEG C for 11-13 hours; adding macromolecular mercaptan, and carrying out heat treatment at 500-600 DEG C; adding Te powder, and carrying out heat treatment at 100-300 DEG C; and adding SeS2, grinding, and carrying out heat treatment at 170-200 DEG C, thereby obtaining the product. The composite electrode prepared by the invention has high SeS2 loading capacity, the shuttle effect of polysulfide and polyselenide is reduced, the lithium ion diffusion energy barrier is reduced, and the rate capability of the Li-SeS2 battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite electrodes and relates to a high SeS 2 Preparation method of loaded Te modified SnS / biocarbon composite electrode. Background Art

[0002] The depletion of fossil energy and the rapid growth of the electronic product market have led to a large increase in the demand for lithium secondary batteries. Currently, commercial lithium-ion batteries cannot meet the needs of high capacity and fast charging due to their limited capacity. Therefore, the demand for high-capacity and high-rate batteries is imminent. Lithium-sulfur batteries have a high theoretical specific capacity (1673mAh·g -1 ) and is environmentally friendly, which has attracted widespread attention from researchers [L.Zhou, D.Danilov, R.Eichel and P.Notten, Host Materials Anchoring Polysulfides in Li-S Batteries Reviewed, Adv.Energy Mater., 2020, 1: 2001304.]. However, the poor conductivity of sulfur makes the research of lithium-sulfur battery electrode materials face many challenges [Z.Shan, Y.He, N.Liu, J.Li, M.Li and Y.Zhang, Spontaneously rooting carbon nanotube incorporated N-doped carbon nanofibers as efficient sulfurhost toward high performance lithium-sulfur batteries. Appl.Surf.Sci., 2021, 539: 148209-148219.]. In order to improve the conductivity of the sulfur electrode, researchers usually introduce carbon materials with strong conductivity to optimize the structure of the sulfur electrode. Since the surface polarity of carbon materials is weak and the polarity of sulfur is strong, the binding energy between sulfur and carbon is weak, generally physical binding, which is not conducive to ensuring the stability of the composite structure, especially at high current density. Se has similar physical and chemical properties to S and has strong conductivity (10 -3 S·m -1), sulfur-selenium solid solution has strong chemical binding force. The above advantages indicate that Se can replace S to become a new generation of battery system [Y.Zhang, Y.Guo, B.Wang, Y.Wei, P.Jing, H.Wu, Z.Dai, M.Wang and Y.Zhang, Carbon, 2020, 161: 413-422. H.Wang, F.Xiao, P.Liu, Y.Zhang, Y.Qi and M.Xu, Hollow carbon spheres loaded with NiSe 2 nanoplates as multifunctional SeS 2 hosts for Li-SeS 2 batteries, J. Colloid Interf. Sci., 2022, 608: 2760-2767.]. However, the development prospects of lithium-selenium batteries are still limited, mainly due to the high cost of selenium and the low mass-to-capacity of lithium-selenium batteries (675 mAh g -1 )[J.Cong,Z.Zheng,J.Hao,H.You,X.Liu and H.Yang,.Hierarchical cathode from hollow CoP embedded in graphenenanosheets to synergistically confine SeS 2 for advanced Li / SeS 2 batteries, J. Alloy Compd., 2021, 867: 159089.]. If the advantages of S and Se can be combined to prepare Li-SeS 2 Batteries will effectively solve the problems of poor conductivity of sulfur and high cost of selenium, and achieve high-capacity storage. 2 Although the battery can solve the problem of low theoretical capacity (Li-SeS 2 The theoretical capacity of the battery is 1345mAh g -1 ), poor conductivity and high cost, but there are still many problems to be solved. Like lithium-sulfur batteries and lithium-selenium batteries, Li-SeS 2The main problem faced by the battery is also the shuttle effect of polysulfides and polyselenides, especially at high current density. Due to the similar reaction mechanism, this problem can be solved by referring to the modification method of lithium-sulfur batteries. Researchers have now discovered a variety of feasible solutions, among which constructing a porous structure and introducing a catalyst are optimization methods for electrode materials, but the disadvantage of the method of introducing a porous structure is that the surface polarity is weak, the capture ability of polysulfides and polyselenides is poor, and structural damage is prone to occur under high current conditions. In addition to enhancing the capture ability of polysulfides and polyselenides, the catalyst can also accelerate the conversion of polysulfides and polyselenides. Therefore, the catalyst can inhibit the shuttle effect of polysulfides and polyselenides at high current density and improve Li-SeS 2 Although the catalyst has high catalytic activity and strong adsorption capacity, its limited conductivity and low porosity are not conducive to achieving high SeS 2 Load. It is necessary to select a material with high porosity and strong electrical conductivity. Summary of the invention

[0003] In order to solve the above problems, the present invention provides a high SeS 2 Preparation method of Te-modified SnS / biocarbon composite electrode with high SeS 2 The loading capacity of Li-SeS increases the adsorption and conversion capacity of polysulfide and polyselenide, reduces the shuttle effect of polysulfide and polyselenide, reduces the lithium ion diffusion energy barrier, and improves the Li-SeS 2 Battery rate performance.

[0004] The technical solution adopted by the present invention is a high SeS 2 The preparation method of the loaded Te modified SnS / biocarbon composite electrode comprises the following steps:

[0005] S1: Lepidopsis, phyllopore and honeycomb materials are mixed at a molar mass ratio of 1: (0.3-0.5): (0.4-0.6) and ground for 30-60 min to obtain biomass raw material A. The relative content of polyporous bacteria materials is controlled to regulate the pore structure. The three-dimensional polyporous bacteria are used in the subsequent reaction process to undergo a dehydration condensation reaction with the products of gluconic acid, hyaluronic acid and lactic acid to obtain porous carbon with a high degree of graphitization, thereby improving the Li 2 S and Li 2 The conductivity of Se.

[0006] S2: Weigh 1.0-5.0 g of biomass raw material A into a beaker, add 50-100 mL, 5-8 mol / L gluconic acid (C 4 H 6 O 6 , Aladdin, analytical grade), hyaluronic acid ((C 14 H21 NO 11 ) n , Aladdin, analytical grade) and lactic acid (C 3 H 6 O 3 , Aladdin, analytical grade) (the molar ratio of gluconic acid, hyaluronic acid and lactic acid is controlled to be (0.2-0.4): (0.1-0.6): (0.3-0.9)), stirred evenly, and then placed in a hydrothermal kettle for solvent thermal reaction after magnetic stirring for 10-30 minutes. The product is washed, filtered and dried to obtain biochar precursor B. In the preparation process of biochar precursor, a mixed solution of gluconic acid, hyaluronic acid and lactic acid is used as a solvent. Gluconic acid is an acid containing a carboxyl group, lactic acid and hyaluronic acid are acids containing both carboxyl and hydroxyl groups, and hyaluronic acid is a high molecular polymer. Gluconic acid, lactic acid and hyaluronic acid are all organic acids, which are more closely combined with biomass raw materials during the hydrothermal reaction, which is conducive to obtaining a biomass precursor with stable structure. By regulating the relative contents of gluconic acid, hyaluronic acid and lactic acid, the relative contents of carboxyl and hydroxyl groups in the biomass precursor are changed, thereby optimizing the number of active sites in the biochar precursor.

[0007] S3: Weigh 1.0-5.0g of biochar precursor B, and continue to add 50-100mL, 5-8mol / L gluconic acid (C 4 H 6 O 6 , Aladdin, analytical grade), hyaluronic acid ((C 14 H 21 NO 11 ) n , Aladdin, analytical grade) and lactic acid (C 3 H 6 O 3 , Aladdin, analytical grade) (the molar ratio of gluconic acid, hyaluronic acid and lactic acid is controlled to be (0.2-0.4): (0.1-0.6): (0.3-0.9)), stirred evenly with a glass rod and placed in a microwave-ultraviolet-ultrasonic trinity synthesis extraction reactor (UWave-1000, Shanghai Xinyi). Biochar C with rich active sites and high conductivity was obtained.

[0008] The microwave-ultraviolet-ultrasound trinity synthesis extraction reactor is used to perform secondary treatment on the biochar precursor to introduce more active sites. The microwave-ultraviolet-ultrasound trinity synthesis extraction reactor uses three different energy sources, namely microwave heating, ultraviolet irradiation and ultrasonic oscillation, to achieve secondary reaction of the biochar precursor and the mixed solution to obtain more active sites (oxygen-containing functional groups).

[0009] S4: The biochar C is heat treated at 550-850℃, and the product is washed, filtered and dried to obtain biochar D with a higher degree of graphitization. The porous fungus material mainly contains rich proteins, fats and polysaccharides. During the heat treatment, a dehydration condensation reaction occurs to obtain a carbon material with a stable structure and rich pore structure, which is conducive to the subsequent SnS loading and Te doping. Due to the different species of bacteria, the internal pore structure is different. Lepidoptera, phyllopores and honeycomb fungi have semicircular, spherical and hexagonal pore structures, respectively. The pore structure has a great influence on the adsorption capacity of carbon materials. By regulating the relative content of lepidoptera, phyllopores and honeycomb fungi, the pore structure of biochar can be precisely controlled. The rich pores in the porous carbon material not only provide sufficient space for sulfur loading, but also provide effective ion transmission channels, which can alleviate the volume expansion caused by the conversion of polysulfide and polyselenide, and reduce Li-SeS 2 The shuttle effect of the battery improves the Li-SeS 2 The rate performance of the battery.

[0010] S5: Weigh 1.0-5.0 g of biochar D into a beaker and add 100-200 mL of ethylene glycol (CH 2 OH) 2 , Aladdin, analytical grade), 0.5-2.5g of alkyl tin compound, and then stirred for 10-40min. The mixed solution was placed in a hydrothermal reactor for solvent thermal reaction. After uniform reaction at 170-180°C for 11-13h, it was washed and dried to obtain SnO 2 / Biocarbon Composites E.

[0011] S6: Weigh 1.0-2.0g SnO 2 / biocarbon composite material E is uniformly mixed with high molecular weight thiol (R-SH, R is alkyl) (SnO 2 The molar mass ratio of SnS to R-SH is 1:(1.2-1.8). The mixture is placed in a low temperature tube furnace, heated from room temperature to 500-600°C at a rate of 5-10°C per minute under vacuum conditions, and kept warm for 1-3 hours to obtain SnS / biocarbon composite material F.

[0012] S7: 1.0-2.0 g SnS / biocarbon composite material F and 0.01-0.4 g Te powder are uniformly mixed, and heat treated at 100-300° C. for 1-3 h to obtain Te-modified SnS / biocarbon composite material G.

[0013] Te is not Li-SeS 2Battery charge and discharge product. The purpose of Te modification of SnS / biochar is to modify the surface of SnS / biochar, so that its surface has more active functional groups with unpaired electrons, and to increase the interlayer distance between SnS and biochar in the SnS / biochar composite material (SnS and biochar itself are two-dimensional layered structures). Te modification of SnS / biochar has a two-dimensional layered structure, which is conducive to the rapid transmission of lithium ions and improves SeS 2 Loading amount. In addition, Te-modified biochar has a high electron donating ability, which improves its surface activity, is conducive to the adsorption of polysulfides and promotes the conversion of polysulfides. Te-modified SnS improves the carrier mobility, promotes electron transfer, and improves the catalytic ability of SnS. Te-modified SnS and Te-modified biochar are combined through Te-O bonds and Sn-Te bonds, and the binding ability is strong, making the composite structure more stable. Therefore, Te-modified SnS / biochar carrier has strong surface activity, large interlayer spacing, high conductivity and good structural stability. Too high doping temperature of Te powder may produce TeO 2 , which is a byproduct of the reaction and is not conducive to maintaining the structural stability of the composite material. If the doping temperature of Te powder is too low, the reaction may not occur.

[0014] S8: Te modified SnS / biocarbon composites G and SeS 2 The mixture is mixed in a mass ratio of (1-3): (7-9), ground, and heat treated at 170-200°C to obtain the product.

[0015] Furthermore, in S1, the materials of Lepidium, Facies and Honeycomb come from traditional Chinese medicine residues.

[0016] Furthermore, in S2, the solvent thermal reaction temperature is 120-160°C, and the reaction is uniformly carried out for 6-8 hours (horizontally placed) to obtain the reaction product.

[0017] Furthermore, in S3, the microwave power is 10-200 W, the ultraviolet power is 10-40 W, the ultrasonic power is 50-300 W, and the processing time is 0.5-1.0 h.

[0018] Furthermore, in S2, the reaction product is washed with water for 3-5 times, filtered with a suction filter, and dried in an oven at 40-75°C for 12-24 hours to obtain a biochar precursor B; after the insulation in S3 is completed, the product is washed with deionized water for 3-5 times, filtered with a suction filter, and dried in an oven at 40-75°C for 12-24 hours to obtain a biochar C with rich active sites and high conductivity.

[0019] Furthermore, in S4, the protective atmosphere is a mixed gas of argon and nitrogen, the volume ratio of argon and nitrogen is 60-75%:25-40%, the gas flow rate is 10-100 sccm; the heating rate is 8-12°C / min, and the insulation time is 1-3h.

[0020] Further, in S4, the product is treated with 50 mL of anhydrous ethanol (C 2 H 6 O, Aladdin, analytical grade) and 50-100 mL of water, and then filtered 3-6 times, and dried in an oven at 50-75° C. for 12-24 h to obtain biochar D with a high degree of graphitization; in S5, the product was washed with anhydrous ethanol (C 2 H 6 O, Aladdin, analytical grade) and deionized water for 3-6 times, and dried in an oven at 65-75°C for 12-24h to obtain SnO 2 / Biocarbon Composites E.

[0021] Furthermore, in S5, the molecular formula of the alkyl tin compound is R n S X 4-n , n=1-4, R is an alkyl group, and X is oxygen, sulfur, chlorine, bromine, iodine or an organic acid.

[0022] Furthermore, in S7, the SnS / biocarbon composite material F and Te powder are mixed in an argon atmosphere, and the protective gas for heat treatment is a mixed gas of argon and hydrogen, and the volume ratio of argon to hydrogen is 90-95%:5%-10%.

[0023] Furthermore, in the S8, Te modified SnS / biocarbon composite material G and SeS 2 After grinding in a glass mortar for 10-30 minutes, the mixture was placed in a low-temperature tube furnace and heated from room temperature to 170-200°C at a rate of 8-12°C per minute under vacuum conditions for 12-24 hours to obtain SeS 2 Loaded Te modified SnS / biocarbon composite electrode H.

[0024] The beneficial effects of the present invention are:

[0025] The present invention uses Te modified SnS / biocarbon composite material as SeS 2 Preparation of Li-SeS with high rate performance 2Batteries, biochar has abundant oxygen-containing functional groups on its surface after heat treatment, which provides sufficient active sites for SnS loading and Te surface modification and has excellent conductivity. Te-modified SnS has abundant anion active sites, which is conducive to the rapid adsorption of lithium ions on the electrode surface, laying the foundation for the generation and conversion of polysulfide and polyselenide. Te-modified SnS / biochar composites have more surface active sites, which is conducive to achieving higher SeS 2 Load. In Li-SeS 2 During the battery charge and discharge process, Te modified SnS / biocarbon carrier is beneficial to inhibit the shuttle effect of polysulfide and polyselenide, achieving better Li-SeS 2 Battery rate performance.

[0026] Traditional Chinese medicine residues containing Leptomyces, Facies and Honeycomb are important biomass resources, but traditional treatment methods such as landfill or incineration are costly, wasteful of resources and may cause secondary pollution, while treatment methods such as composting, edible fungus cultivation, and feed processing have many drawbacks in practical applications. The technical solution of the present invention not only helps to eliminate or reduce the pollution of traditional Chinese medicine residues to the environment, but more importantly, turns waste into treasure, makes it a resource, and makes full use of it. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 This is the SEM image of the Te-modified SnS / biocarbon composite material obtained in Example 3.

[0029] Figure 2 This is the SEM image of the Te-modified SnS / biocarbon composite material obtained in Example 9. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Embodiment 1,

[0032] A high SeS 2The preparation method of the loaded Te modified SnS / biocarbon composite electrode comprises the following steps:

[0033] S1: Select discarded Lepidium, Polypore and Alveolar materials from medical treatment (traditional Chinese medicine residues) in a molar mass ratio of 1:0.3:0.4 as raw materials and grind them in a mortar for 60 minutes to obtain biomass raw material A.

[0034] S2: Weigh 2.0 g of biomass raw material A into a beaker, add 100 mL, 7 mol / L gluconic acid (C 4 H 6 O 6 , Aladdin, analytical grade), hyaluronic acid ((C 14 H 21 NO 11 ) n , Aladdin, analytical grade) and lactic acid (C 3 H 6 O 3 , Aladdin, analytical grade) (the molar ratio of gluconic acid, hyaluronic acid and lactic acid was controlled to be 0.2:0.2:0.4), stirred evenly with a glass rod and then placed in a hydrothermal kettle for solvothermal reaction after magnetic stirring for 30 minutes. The mixture was uniformly reacted at 160°C for 8 hours (placed horizontally) to obtain a reaction product. The reaction product was washed with water 5 times and then filtered with a suction filter. It was dried in an oven at 70°C for 24 hours to obtain biochar precursor B.

[0035] S3: Weigh 2.0 g of biochar precursor B and continue to add 100 mL of 7 mol / L gluconic acid (C 4 H 6 O 6 , Aladdin, analytical grade), hyaluronic acid ((C 14 H 21 NO 11 ) n , Aladdin, analytical grade) and lactic acid (C 3 H 6 O 3 , Aladdin, analytical grade) (the molar ratio of gluconic acid, hyaluronic acid and lactic acid was controlled to be 0.2:0.2:0.4, stirred evenly with a glass rod and placed in a microwave-ultraviolet-ultrasonic trinity synthesis extraction reactor (UWave-1000, Shanghai Xinyi), with microwave power of 100W, ultraviolet power of 20W, and ultrasonic power of 100W for 1.0h. After the insulation, the product was washed with deionized water for 5 times, filtered with a suction filter, and dried in an oven at 70°C for 24h to obtain biochar C with rich active sites and high conductivity.

[0036] The mixed solutions in step S2 and step S3 are completely the same, which prevents the carboxyl and hydroxyl groups in the mixed acid from cross-linking due to changes in content and concentration, resulting in more side reactions, which is not conducive to the regulation of the relative content of carboxyl and hydroxyl groups in the biochar precursor.

[0037] S4: The biochar C was placed in a tube furnace for heat treatment. Under the protection of a mixed gas of argon and nitrogen (the volume ratio of argon and nitrogen was 70%:30%, and the gas flow rate was 50 sccm), the temperature was raised from room temperature to 600°C at a rate of 10°C / min, and the temperature was kept for 2 hours. The product was quenched with 50 mL of anhydrous ethanol (C 2 H 6 O, Aladdin, analytical grade) and 100 mL of water, filtered 5 times, and dried in an oven at 70 °C for 24 h to obtain biochar D with a high degree of graphitization.

[0038] S5: Weigh 2.0 g of biochar D into a beaker and add 150 mL of ethylene glycol ((CH 2 OH) 2 , Aladdin, analytical grade), 1.0 g alkyl tin compound (R n S X 4-n (n=1, R is alkyl, X is oxygen) and stirred for 30 min, the mixed solution was placed in a hydrothermal reactor for solvent thermal reaction, and after uniform reaction at 180°C for 12 h, anhydrous ethanol (C 2 H 6 O, Aladdin, analytical grade) and washed with deionized water for 5 times, and dried in an oven at 70 °C for 24 h to obtain SnO 2 / Biocarbon Composites E.

[0039] S6: weigh 2.0g SnO 2 / biocarbon composite material E is uniformly mixed with high molecular weight thiol (R-SH, R is alkyl) (SnO 2 The molar mass ratio of SnS to R-SH is 1:1.6). The mixture was placed in a low-temperature tube furnace, heated from room temperature to 550°C at a rate of 10°C per minute under vacuum conditions, and kept warm for 2 hours to obtain SnS / biocarbon composite material F.

[0040] S7: Weigh 2.0g SnS / biocarbon composite material F and 0.1g Te powder and mix them evenly in a glove box filled with argon. Then put them into a low-temperature tubular furnace filled with argon and hydrogen mixed gas (the volume ratio of argon and hydrogen is 95%:5%) for heat treatment at a temperature of 200°C for 2 hours. The product after the reaction is Te-modified SnS / biocarbon composite material G.

[0041] S8: Weigh 2.0 g Te-modified SnS / biocarbon composite material G and mix with SeS 2The mixture was mixed at a mass ratio of 1:9, ground in a glass mortar for 20 min, and then placed in a low-temperature tube furnace. The temperature was raised from room temperature to 180 °C at a rate of 10 °C per minute under vacuum conditions, and reacted in the low-temperature tube furnace for 24 h to obtain SeS 2 Loaded Te modified SnS / biocarbon composite electrode H.

[0042] Embodiment 2,

[0043] A high SeS 2 The preparation method of the loaded Te modified SnS / biocarbon composite electrode comprises the following steps:

[0044] S1: Select discarded Lepidium, Polypore and Alveolar materials from medical treatment (traditional Chinese medicine residues) in a molar mass ratio of 1:0.5:0.6 as raw materials and grind them in a mortar for 60 minutes to obtain biomass raw material A.

[0045] S2: Weigh 2.0 g of biomass raw material A into a beaker, add 100 mL, 7 mol / L gluconic acid (C 4 H 6 O 6 , Aladdin, analytical grade), hyaluronic acid ((C 14 H 21 NO 11 ) n , Aladdin, analytical grade) and lactic acid (C 3 H 6 O 3 , Aladdin, analytical grade) (the molar ratio of gluconic acid, hyaluronic acid and lactic acid was controlled to be 0.2:0.2:0.4, stirred evenly with a glass rod and then placed in a hydrothermal kettle for solvothermal reaction after magnetic stirring for 30 minutes, and reacted evenly at 160°C for 8 hours (placed horizontally) to obtain the reaction product, washed the reaction product with water 5 times and then filtered with a suction filter, and dried in an oven at 70°C for 24 hours to obtain the biocarbon precursor B.

[0046] S3: Weigh 2.0 g of biochar precursor B and continue to add 100 mL of 7 mol / L gluconic acid (C 4 H 6 O 6 , Aladdin, analytical grade), hyaluronic acid ((C 14 H 21 NO 11 ) n , Aladdin, analytical grade) and lactic acid (C 3 H 6 O 3, Aladdin, analytical grade) (the molar ratio of gluconic acid, hyaluronic acid and lactic acid was controlled to be 0.2:0.2:0.4, stirred evenly with a glass rod and placed in a microwave-ultraviolet-ultrasonic trinity synthesis extraction reactor (UWave-1000, Shanghai Xinyi), with microwave power of 100W, ultraviolet power of 20W, and ultrasonic power of 100W for 1.0h. After the insulation, the product was washed with deionized water for 5 times, filtered with a suction filter, and dried in an oven at 70°C for 24h to obtain biochar C with rich active sites and high conductivity.

[0047] S4: The biochar C was placed in a tube furnace for heat treatment. Under the protection of a mixed gas of argon and nitrogen (the volume ratio of argon and nitrogen was 70%:30%, and the gas flow rate was 50 sccm), the temperature was raised from room temperature to 600°C at a rate of 10°C / min, and the temperature was kept for 2 hours. The product was quenched with 50 mL of anhydrous ethanol (C 2 H 6 O, Aladdin, analytical grade) and 100 mL of water, filtered 5 times, and dried in an oven at 70 °C for 24 h to obtain biochar D with a high degree of graphitization.

[0048] S5: Weigh 2.0 g of biochar D into a beaker and add 150 mL of ethylene glycol ((CH 2 OH) 2 , Aladdin, analytical grade), 1.0 g alkyl tin compound (R n S X 4-n (n=4, R is an alkyl group, X is oxygen) and stirred for 30 min. The mixed solution was placed in a hydrothermal reactor for solvent thermal reaction. After uniform reaction at 180°C for 12 h, anhydrous ethanol (C 2 H 6 O, Aladdin, analytical grade) and washed with deionized water for 5 times, and dried in an oven at 70 °C for 24 h to obtain SnO 2 / Biocarbon Composites E.

[0049] S6: weigh 2.0g SnO 2 / biocarbon composite material E is uniformly mixed with high molecular weight thiol (R-SH, R is alkyl) (SnO 2 The molar mass ratio of SnS to R-SH is 1:1.6. The mixture was placed in a low temperature tube furnace, heated from room temperature to 550°C at a rate of 10°C per minute under vacuum conditions, and kept warm for 2 hours to obtain SnS / biocarbon composite material F.

[0050] S7: Weigh 2.0g SnS / biocarbon composite material F and 0.1g Te powder and mix them evenly in a glove box filled with argon. Then put them into a low-temperature tubular furnace filled with a mixed gas of argon and hydrogen (the volume ratio of argon and hydrogen is 95%:5%) for heat treatment at a temperature of 200°C for 2 hours. The product after the reaction is Te-modified SnS / biocarbon composite material G.

[0051] S8: Weigh 2.0 g Te-modified SnS / biocarbon composite material G and mix with SeS 2 The mixture was mixed at a mass ratio of 1:9, ground in a glass mortar for 20 min, and then placed in a low-temperature tube furnace. The temperature was raised from room temperature to 180 °C at a rate of 10 °C per minute under vacuum conditions, and reacted in the low-temperature tube furnace for 24 h to obtain SeS 2 Loaded Te modified SnS / biocarbon composite electrode H.

[0052] Embodiment 3,

[0053] A high SeS 2 The preparation method of the loaded Te modified SnS / biocarbon composite electrode comprises the following steps:

[0054] S1: Polyporus materials such as Lepidium, Polyporus and Polyporus discarded from medical treatment (traditional Chinese medicine residues) were selected as raw materials in a molar mass ratio of 1:0.4:0.5 and were continuously ground in a mortar for 60 minutes to obtain biomass raw material A.

[0055] S2: Weigh 2.0 g of biomass raw material A into a beaker, add 100 mL, 7 mol / L gluconic acid (C 4 H 6 O 6 , Aladdin, analytical grade), hyaluronic acid ((C 14 H 21 NO 11 ) n , Aladdin, analytical grade) and lactic acid (C 3 H 6 O 3 , Aladdin, analytical grade) (the molar ratio of gluconic acid, hyaluronic acid and lactic acid was controlled to be 0.2:0.2:0.4, stirred evenly with a glass rod and then placed in a hydrothermal kettle for solvothermal reaction after magnetic stirring for 30 minutes, and reacted evenly at 160°C for 8 hours (placed horizontally) to obtain the reaction product, washed the reaction product with water 5 times and then filtered with a suction filter, and dried in an oven at 70°C for 24 hours to obtain the biocarbon precursor B.

[0056] S3: Weigh 2.0 g of biochar precursor B and continue to add 100 mL of 7 mol / L gluconic acid (C 4 H 6 O6 , Aladdin, analytical grade), hyaluronic acid ((C 14 H 21 NO 11 ) n , Aladdin, analytical grade) and lactic acid (C 3 H 6 O 3 , Aladdin, analytical grade) (the molar ratio of gluconic acid, hyaluronic acid and lactic acid was controlled to be 0.2:0.2:0.4, stirred evenly with a glass rod and placed in a microwave-ultraviolet-ultrasonic trinity synthesis extraction reactor (UWave-1000, Shanghai Xinyi), with microwave power of 100W, ultraviolet power of 20W, and ultrasonic power of 100W for 1.0h. After the insulation, the product was washed with deionized water for 5 times, filtered with a suction filter, and dried in an oven at 70°C for 24h to obtain biochar C with rich active sites and high conductivity.

[0057] S4: The biochar C was placed in a tube furnace for heat treatment. Under the protection of a mixed gas of argon and nitrogen (the volume ratio of argon and nitrogen was 70%:30%, and the gas flow rate was 50 sccm), the temperature was raised from room temperature to 600°C at a rate of 10°C / min, and the temperature was kept for 2 hours. The product was quenched with 50 mL of anhydrous ethanol (C 2 H 6 O, Aladdin, analytical grade) and 100 mL of water, filtered 5 times, and dried in an oven at 70 °C for 24 h to obtain biochar D with a high degree of graphitization.

[0058] S5: Weigh 2.0 g of biochar D into a beaker and add 150 mL of ethylene glycol ((CH 2 OH) 2 , Aladdin, analytical grade), 1.0 g alkyl tin compound (R n S X 4-n (n=2, R is alkyl, X is oxygen) and stirred for 30 min, the mixed solution was placed in a hydrothermal reactor for solvent thermal reaction, and after uniform reaction at 180°C for 12 h, anhydrous ethanol (C 2 H 6 O, Aladdin, analytical grade) and washed with deionized water for 5 times, and dried in an oven at 70 °C for 24 h to obtain SnO 2 / Biocarbon Composites E.

[0059] S6: weigh 2.0g SnO 2 / biocarbon composite material E is uniformly mixed with high molecular weight thiol (R-SH, R is alkyl) (SnO 2The molar mass ratio of SnS to R-SH is 1:1.6. The mixture was placed in a low temperature tube furnace, heated from room temperature to 550°C at a rate of 10°C per minute under vacuum conditions, and kept warm for 2 hours to obtain SnS / biocarbon composite material F.

[0060] S7: Weigh 2.0g SnS / biocarbon composite material F and 0.1g Te powder and mix them evenly in a glove box filled with argon. Then put them into a low-temperature tubular furnace filled with a mixed gas of argon and hydrogen (the volume ratio of argon and hydrogen is 95%:5%) for heat treatment at a temperature of 200°C for 2 hours. The product after the reaction is Te-modified SnS / biocarbon composite material G.

[0061] S8: Weigh 2.0 g Te-modified SnS / biocarbon composite material G and mix with SeS 2 The mixture was mixed at a mass ratio of 1:9, ground in a glass mortar for 20 min, and then placed in a low-temperature tube furnace. The temperature was raised from room temperature to 180 °C at a rate of 10 °C per minute under vacuum conditions, and reacted in the low-temperature tube furnace for 24 h to obtain SeS 2 Loaded Te modified SnS / biocarbon composite electrode H.

[0062] Embodiment 4,

[0063] A high SeS 2 The preparation method of the loaded Te modified SnS / biocarbon composite electrode is the same as that of Example 3 except that the molar ratio of gluconic acid, hyaluronic acid and lactic acid is controlled to be 0.4:0.2:0.8 in steps S2 and S3.

[0064] Embodiment 5,

[0065] A high SeS 2 The preparation method of the loaded Te modified SnS / biocarbon composite electrode is the same as that of Example 3 except that the molar ratio of gluconic acid, hyaluronic acid and lactic acid is controlled to be 0.2:0.6:0.3 in steps S2 and S3.

[0066] Embodiment 6,

[0067] A high SeS 2 The preparation method of the loaded Te modified SnS / biocarbon composite electrode is the same as that of Example 3 except that the molar ratio of gluconic acid, hyaluronic acid and lactic acid is controlled to be 0.3:0.1:0.9 in steps S2 and S3.

[0068] Embodiment 7,

[0069] A high SeS 2The preparation method of the loaded Te modified SnS / biochar composite electrode is the same as that of Example 3 except that in step S3, the microwave power is 10 W, the UV power is 40 W, the ultrasonic power is 50 W, and the reaction time is 0.8 h.

[0070] Embodiment 8,

[0071] A high SeS 2 The preparation method of the loaded Te modified SnS / biocarbon composite electrode is the same as that of Example 3 except that in step S3, the microwave power is 200 W, the UV power is 10 W, the ultrasonic power is 300 W, and the reaction time is 0.5 h.

[0072] Embodiment 9,

[0073] A high SeS 2 The preparation method of the loaded Te modified SnS / biocarbon composite electrode is the same as that of Example 3 except that the amount of Te powder added in step S7 is 0.01 g.

[0074] Embodiment 10,

[0075] A high SeS 2 The preparation method of the loaded Te modified SnS / biocarbon composite electrode is the same as that of Example 3 except that the amount of Te powder added in step S7 is 0.4 g.

[0076] Embodiment 11,

[0077] A high SeS 2 The preparation method of the loaded Te modified SnS / biocarbon composite electrode comprises the following steps:

[0078] S1: Polyporus materials such as Lepidium, Polyporus and Honeycomb were selected from medical (traditional Chinese medicine residues) with a molar mass ratio of 1:0.4:0.5 as raw materials and were continuously ground in a mortar for 30 minutes to obtain biomass raw material A.

[0079] S2: Weigh 1.0 g of biomass raw material A into a beaker, add 80 mL of 5 mol / L gluconic acid (C 4 H 6 O 6 , Aladdin, analytical grade), hyaluronic acid ((C 14 H 21 NO 11 ) n , Aladdin, analytical grade) and lactic acid (C 3 H 6 O 3, Aladdin, analytical grade) (the molar ratio of gluconic acid, hyaluronic acid and lactic acid was controlled to be 0.2:0.2:0.4, stirred evenly with a glass rod and then placed in a hydrothermal kettle for solvothermal reaction after magnetic stirring for 10 minutes, and reacted evenly at 120°C for 7 hours (placed horizontally) to obtain the reaction product, washed the reaction product with water 3 times and filtered with a suction filter, and dried in an oven at 75°C for 12 hours to obtain the biocarbon precursor B.

[0080] S3: Weigh 1.0 g of biochar precursor B and continue to add 80 mL of 5 mol / L gluconic acid (C 4 H 6 O 6 , Aladdin, analytical grade), hyaluronic acid ((C 14 H 21 NO 11 ) n , Aladdin, analytical grade) and lactic acid (C 3 H 6 O 3 , Aladdin, analytical grade) (the molar ratio of gluconic acid, hyaluronic acid and lactic acid was controlled to be 0.2:0.2:0.4, stirred evenly with a glass rod and placed in a microwave-ultraviolet-ultrasonic trinity synthesis extraction reactor (UWave-1000, Shanghai Xinyi), with microwave power of 100W, ultraviolet power of 20W, and ultrasonic power of 100W for 1.0h. After the insulation, the product was washed with deionized water for 3 times, filtered with a suction filter, and dried in an oven at 75°C for 12h to obtain biochar C with rich active sites and high conductivity.

[0081] S4: The biochar C was placed in a tube furnace for heat treatment. Under the protection of a mixed gas of argon and nitrogen (the volume ratio of argon and nitrogen was 60%:40%, and the gas flow rate was 10 sccm), the temperature was raised from room temperature to 550°C at a rate of 12°C / min, and the temperature was kept for 3 hours. The product was heated with 50 mL of anhydrous ethanol (C 2 H 6 O, Aladdin, analytical grade) and 50 mL of water, washed and filtered three times, and dried in an oven at 75 °C for 12 h to obtain biochar D with a high degree of graphitization.

[0082] S5: Weigh 1.0 g of biochar D into a beaker and add 200 mL of ethylene glycol (CH 2 OH) 2 , Aladdin, analytical grade), 0.5 g alkyl tin compound (R n S X 4-n (n=2, R is an alkyl group, X is oxygen) and stirred for 40 min. The mixed solution was placed in a hydrothermal reactor for solvent thermal reaction. After uniform reaction at 170°C for 13 h, anhydrous ethanol (C 2 H6 O, Aladdin, analytical grade) and washed with deionized water for 3 times, and dried in an oven at 75 °C for 12 h to obtain SnO 2 / Biocarbon Composites E.

[0083] S6: SnO 2 / biocarbon composite material E and high molecular weight thiol (R-SH, R is alkyl) are uniformly mixed, SnO 2 The molar mass ratio of the SnS / biocarbon composite material F was 1:1.8. The mixture was placed in a low temperature tube furnace, heated from room temperature to 600°C at a rate of 5°C per minute under vacuum conditions, and kept warm for 1 hour to obtain the SnS / biocarbon composite material F.

[0084] S7: Weigh 1.0g SnS / biocarbon composite material F and 0.4g Te powder and mix them evenly in a glove box filled with argon, and then put them into a low-temperature tubular furnace filled with argon and hydrogen mixed gas (argon and hydrogen volume ratio is 90%:10%) for heat treatment at a temperature of 300°C for 1h. The product after the reaction is Te-modified SnS / biocarbon composite material G.

[0085] S8: Weigh 2.0 g Te-modified SnS / biocarbon composite material G and mix with SeS 2 The mixture was mixed in a mass ratio of 3:7, ground in a glass mortar for 10 min, and then placed in a low-temperature tube furnace. The temperature was raised from room temperature to 200 °C at a rate of 8 °C per minute under vacuum conditions, and reacted in a low-temperature tube furnace for 12 h to obtain SeS 2 Loaded Te modified SnS / biocarbon composite electrode H.

[0086] Embodiment 12,

[0087] A high SeS 2 The preparation method of the loaded Te modified SnS / biocarbon composite electrode comprises the following steps:

[0088] S1: Polyporus materials such as Lepidium, Polyporus and Polyporus discarded from medical treatment (traditional Chinese medicine residues) were selected as raw materials in a molar mass ratio of 1:0.4:0.5 and were continuously ground in a mortar for 40 minutes to obtain biomass raw material A.

[0089] S2: Weigh 5.0 g of biomass raw material A into a beaker, add 50 mL of 8 mol / L gluconic acid (C 4 H 6 O 6 , Aladdin, analytical grade), hyaluronic acid ((C 14 H 21 NO 11 ) n , Aladdin, analytical grade) and lactic acid (C 3 H6 O 3 , Aladdin, analytical grade) (the molar ratio of gluconic acid, hyaluronic acid and lactic acid was controlled to be 0.2:0.2:0.4, stirred evenly with a glass rod and then placed in a hydrothermal kettle for solvothermal reaction after magnetic stirring for 10 minutes, and reacted evenly at 140°C for 6 hours (placed horizontally) to obtain the reaction product, washed the reaction product with water 4 times and then filtered with a suction filter, and dried in an oven at 40°C for 18 hours to obtain the biocarbon precursor B.

[0090] S3: Weigh 5.0 g of biochar precursor B and continue to add 50 mL of 8 mol / L gluconic acid (C 4 H 6 O 6 , Aladdin, analytical grade), hyaluronic acid ((C 14 H 21 NO 11 ) n , Aladdin, analytical grade) and lactic acid (C 3 H 6 O 3 , Aladdin, analytical grade) (the molar ratio of gluconic acid, hyaluronic acid and lactic acid was controlled to be 0.2:0.2:0.4, stirred evenly with a glass rod and placed in a microwave-ultraviolet-ultrasonic trinity synthesis extraction reactor (UWave-1000, Shanghai Xinyi), with microwave power of 100W, ultraviolet power of 20W, and ultrasonic power of 100W for 1.0h. After the insulation, the product was washed with deionized water for 4 times, filtered with a suction filter, and dried in an oven at 40°C for 18h to obtain biochar C with rich active sites and high conductivity.

[0091] S4: The biochar C was placed in a tube furnace for heat treatment. Under the protection of a mixed gas of argon and nitrogen (the volume ratio of argon and nitrogen was 75%:25%, and the gas flow rate was 100 sccm), the temperature was raised from room temperature to 850°C at a rate of 8°C / min, and the temperature was kept for 1 hour. The product was quenched with 500 mL of anhydrous ethanol (C 2 H 6 O, Aladdin, analytical grade) and 50 mL of water, washed and filtered 6 times, and dried in an oven at 50 °C for 20 h to obtain biochar D with a high degree of graphitization.

[0092] S5: Weigh 5.0 g of biochar D into a beaker and add 100 mL of ethylene glycol (CH 2 OH) 2 , Aladdin, analytical grade), 2.5 g alkyl tin compound (R n S X 4-n(n=4, R is an alkyl group, X is oxygen) and stirred for 10 min. The mixed solution was placed in a hydrothermal reactor for solvent thermal reaction. After uniform reaction at 175°C for 11 h, anhydrous ethanol (C 2 H 6 O, Aladdin, analytical grade) and washed with deionized water for 3 times, and dried in an oven at 75 °C for 12 h to obtain SnO 2 / Biocarbon Composites E.

[0093] S6: SnO 2 / biocarbon composite material E and high molecular weight thiol (R-SH, R is alkyl) are uniformly mixed, SnO 2 The molar mass ratio of the SnS / biocarbon composite material F was 1:1.2. The mixture was placed in a low temperature tube furnace, heated from room temperature to 500°C at a rate of 5°C per minute under vacuum conditions, and kept warm for 3 hours to obtain the SnS / biocarbon composite material F.

[0094] S7: Weigh 1.5g SnS / biocarbon composite material F and 0.01g Te powder and mix them evenly in a glove box filled with argon, and then put them into a low-temperature tubular furnace filled with argon and hydrogen mixed gas (argon and hydrogen volume ratio is 90%:10%) for heat treatment at a temperature of 100°C for 3h. The product after the reaction is Te-modified SnS / biocarbon composite material G.

[0095] S8: Weigh 2.0 g Te-modified SnS / biocarbon composite material G and mix with SeS 2 The mixture was mixed at a mass ratio of 2:8, ground in a glass mortar for 30 min, and then placed in a low-temperature tube furnace. The temperature was raised from room temperature to 170 °C at a rate of 12 °C per minute under vacuum conditions. The mixture was reacted in a low-temperature tube furnace for 18 h to obtain SeS 2 Loaded Te modified SnS / biocarbon composite electrode H.

[0096] SeS prepared in Examples 1 to 12 2 The electrochemical performance of the Te-modified SnS / biocarbon composite electrode was tested, and the test results are shown in Table 1.

[0097] The pores of the biochar prepared in the embodiment of the present invention are three-dimensional structures, the pores are evenly distributed and the pore size is adjustable. From the test results of Example 1, Example 2 and Example 3, it can be seen that by controlling the relative proportions of Lepidium, Laminaria and Honeycomb, the obtained biochar has different porous structures. The regulation of pore structure is of great significance for optimizing the ion diffusion path and regulating the adsorption capacity of polysulfide and polyselenide.

[0098] The pore size, pore shape, and pore distribution will change with the relative content of the pores of the pores, pores, and honeycomb fungi. The shape of the pores is affected by the structure of the pores, pores, and honeycomb fungi. The pores of the pores, pores, and honeycomb fungi have semicircular, spherical, and hexagonal pore structures, respectively. The pore size is affected by the thickness of the bacterial wall. The wall thickness of the pores of the pores, pores, and honeycomb fungi is 0.2-0.8cm, 0.3-0.4cm, and 0.1-0.2cm, respectively. After the same process treatment, the pores of the pores are more likely to have small holes than the honeycomb fungi due to the thicker bacterial wall. The pore size distribution is affected by the properties of the material itself and the heat treatment temperature. Honeycomb fungi contain more proteins, fats, reducing sugars, etc. The pores contain more polysaccharides and phenolic compounds. The main component of the pores is polysaccharides. Therefore, after the same heat treatment process, the pores of the pores are more likely to obtain a uniform pore size distribution.

[0099] The purpose of regulating the molar mass ratio of the pores of the pores of the pores of the pores, the pores of the layer and the honeycomb in the embodiment of the present invention is to obtain porous carbon with a suitable pore size and uniform pore size. Honeycomb contains more proteins, fats, reducing sugars, etc. Since proteins and fats are not easy to decompose, the structure is relatively stable, and more benzene ring structures are obtained during the heat treatment process. The pores contain more polysaccharides and phenolic compounds, which are easily decomposed to obtain more short-chain COH bonds and Ar-OH bonds during the heat treatment process. The main component of the pores is polysaccharides, which have a relatively unstable structure and are easily decomposed to obtain more short-chain COH bonds. If the content of the pores exceeds the range, the content of COH bonds and Ar-OH bonds will increase. If the content of the honeycomb exceeds the range, the content of the benzene ring structure will increase. Compared with COH bonds, the surface activity of Ar-OH bonds and benzene ring structures is weak, which is not conducive to the production of abundant oxygen-containing functional groups on the surface of biochar.

[0100] If only honeycomb bacteria are added, the surface activity is weak, which is not conducive to the production of abundant oxygen-containing functional groups on the surface of biochar, further affecting the loading amount of Te-modified SnS. If only phyllopore bacteria are added, the structure is unstable and the surface activity is weak, which is not conducive to the loading of Te-modified SnS and maintaining the stability of the composite structure. If only phyllopore bacteria are added, the structure will be unstable, which is not conducive to maintaining the stability of the composite structure.

[0101] From the test results of Example 3, Example 4, Example 5, and Example 6, it can be seen that controlling the relative molar ratio of gluconic acid, hyaluronic acid, and lactic acid can optimize the relative content of carboxyl and hydroxyl groups on the surface of the composite material. 2 The binding energy of high SeS 2 Te-loaded SnS / biocarbon composite electrode in Li-SeS 2 Structural stability in batteries.

[0102] From the test results of Example 3, Example 7, and Example 8, it can be seen that controlling microwave power, ultraviolet power, and ultrasonic power can enhance the ability of carboxyl and hydroxyl groups in gluconic acid, hyaluronic acid, and lactic acid to bind to biochar, thereby generating a richer pore structure that is conducive to the diffusion of lithium ions. Under the regulation of microwave power, ultraviolet power, and ultrasonic power, the graphitization degree of the composite material is further improved, which improves the transmission rate of electrons, providing a basis for the preparation of high-rate performance Li-SeS 2 Batteries laid the foundation.

[0103] From the test results of Example 3, Example 9, and Example 10, it can be seen that controlling the amount of Te powder added and optimizing the number of active sites on the surface of the SnS / biocarbon composite material can make the composite material have a high electron-donating ability, which is conducive to adsorbing polysulfides and promoting polysulfide conversion. In addition, regulating the amount of Te added is conducive to improving carrier mobility, promoting electron transport, and improving the catalytic ability of SnS. Figure 1 and Figure 2 It can be seen that increasing the amount of Te powder added increases the porosity of SnS / biocarbon composites, makes the pore size more uniform, and increases the active sites, which is conducive to the adsorption of polysulfide and polyselenide, and improves the Li-SeS 2 The rate performance of the battery.

[0104] The addition of Te powder in the embodiment of the present invention increases the porosity of the SnS / biocarbon composite material and makes the pore size more uniform; when the Te powder content is too high, too much Te will replace Sn in SnS to obtain TeS, which increases the instability of the composite material, reduces the conductivity, and reduces the cycle stability of the composite electrode. When the Te powder content is too low, too few defects are introduced into the SnS / biocarbon composite material, which is not conducive to SeS 2 The load is not conducive to the capture of polysulfide and polyselenide during the charge and discharge process, and reduces the capacity of the composite electrode.

[0105] Table 1SeS 2 Loading amount and Li-SeS 2 Comparison table of battery cycle performance results

[0106]

[0107]

[0108] In the embodiment of the present invention, Lepidium, Facies and Alveolar are selected as biocarbon sources, specifically all species under the genera Lepidium, Facies and Alveolar; their relative proportions are changed, the pore structure is optimized, and the biocarbon material is obtained by solvent thermal reaction, microwave-ultraviolet-ultrasound method and tube furnace heat treatment. The surface active functional groups (carboxyl and hydroxyl) are rich, which is conducive to the loading of SnS, and the SnS / biocarbon composite material is obtained. The surface of the SnS / biocarbon composite material is modified by Te atom doping, so that the surface has more active functional groups with unpaired electrons, the interlayer distance between SnS and biocarbon in the SnS / biocarbon composite material is increased (SnS and biocarbon themselves are two-dimensional layered structures), and SeS is increased. 2 Loading capacity. Te modified biochar has high electron donating ability, improves its surface activity, is conducive to the adsorption of polysulfides and promotes the conversion of polysulfides. Te modified SnS and Te modified biochar are combined through Te-O bonds and Sn-Te bonds, and the binding ability is strong, making the composite structure more stable during the charge and discharge process. In the embodiment of the present invention, Te modified SnS / biochar carrier is first prepared, and polysulfide and polyselenide are adsorbed during the reaction process, and then Li 2 S and Li 2 Se, overcome Li 2 S and Li 2 The problem of Se's poor solubility in the electrolyte.

[0109] Traditional Chinese medicine residues are waste residues produced after the extraction and processing of traditional Chinese medicines. They are not only underutilized biomass resources, but also potential sources of environmental pollution. For traditional Chinese medicine pharmaceutical companies, according to the "Law on the Prevention and Control of Environmental Pollution by Solid Waste", drug residues belong to general industrial solid wastes and should be disposed of in accordance with the "Pollution Control Standards for General Industrial Solid Waste Storage and Disposal Sites". However, due to the small number of industrial solid waste storage and disposal sites, and the fact that domestic waste landfills generally do not accept industrial solid waste, most traditional Chinese medicine pharmaceutical companies choose to hand over traditional Chinese medicine residues to qualified related companies for burial and treatment, and rarely track them themselves. Therefore, the research prospects for traditional Chinese medicine residues are very broad. The research is not only about eliminating or reducing the pollution of traditional Chinese medicine residues to the environment, but more importantly, it is about making it a resource and making full use of it.

[0110] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention are included in the protection scope of the present invention.

Claims

1. A method for preparing a Te-modified SnS / biocarbon composite electrode with high SeS2 loading, characterized in that: The following steps are involved: S1: Mix the materials of Lepidium, Polypore and Alveolar Fungus at a molar mass ratio of 1: (0.3-0.5): (0.4-0.6), grind and obtain biomass raw material A; S2: 1.0-5.0 g of biomass raw material A is stirred evenly with 50-100 mL of a 5-8 mol / L mixed solution, wherein the mixed solution is obtained by mixing gluconic acid, hyaluronic acid and lactic acid in a molar ratio of (0.2-0.4): (0.1-0.6): (0.3-0.9); after a solvent thermal reaction, the product is washed, filtered and dried to obtain a biochar precursor B; S3: 1.0-5.0 g of biochar precursor B is stirred evenly with the mixed solution, and the ratio and amount of the mixed solution are the same as S2; then, the biochar C is obtained by microwave heating, ultraviolet irradiation and ultrasonic oscillation treatment; S4: heat treating the biochar C at 550-850°C, washing, filtering and drying the product to obtain biochar D with a higher degree of graphitization; S5: 1.0-5.0 g of biochar D, 100-200 mL of ethylene glycol and 0.5-2.5 g of an alkyl tin compound are stirred evenly, subjected to hydrothermal reaction at 170-180° C. for 11-13 h, washed and dried to obtain a SnO2 / biochar composite material E; S6: uniformly mixing the SnO2 / biocarbon composite material E and the polymer thiol, wherein the molar mass ratio of SnO2 to the polymer thiol is 1:(1.2-1.8), heat treating at 500-600°C, and keeping the temperature for 1-3h to obtain the SnS / biocarbon composite material F; S7: 1.0-2.0 g SnS / biocarbon composite material F and 0.01-0.4 g Te powder are uniformly mixed, and heat treated at 100-300° C. for 1-3 h to obtain Te-modified SnS / biocarbon composite material G; S8: Mix Te-modified SnS / biocarbon composite material G and SeS2 in a mass ratio of (1-3):(7-9), grind, and heat treat at 170-200°C to obtain.

2. The method for preparing a Te-modified SnS / biocarbon composite electrode with high SeS2 loading according to claim 1, characterized in that: In S1, the materials of Lepidium, Folidium and Alveolar are from the residues of traditional Chinese medicine.

3. The method for preparing a Te-modified SnS / biocarbon composite electrode with high SeS2 loading according to claim 1, characterized in that: In S2, the solvent thermal reaction temperature is 120-160° C., and the uniform reaction time is 6-8 hours.

4. The method for preparing a Te-modified SnS / biocarbon composite electrode with high SeS2 loading according to claim 1, characterized in that: In S3, the microwave power is 10-200W, the ultraviolet power is 10-40W, the ultrasonic power is 50-300W, and the processing time is 0.5-1.0h.

5. The method for preparing a Te-modified SnS / biocarbon composite electrode with high SeS2 loading according to claim 1, characterized in that: The washing, filtration and drying in S2 are specifically as follows: washing with water for 3-5 times, filtering with a suction filter, and drying in an oven at 40-75° C. for 12-24 hours.

6. The method for preparing a Te-modified SnS / biocarbon composite electrode with high SeS2 loading according to claim 1, characterized in that: In S4, the protective atmosphere is a mixed gas of argon and nitrogen, the volume ratio of argon and nitrogen is 60-75%:25-40%, the gas flow rate is 10-100 sccm; the heating rate is 8-12°C / min, and the insulation is 1-3h.

7. The method for preparing a Te-modified SnS / biocarbon composite electrode with high SeS2 loading according to claim 1, characterized in that: In the S4, the product is washed with anhydrous ethanol and water in turn and filtered 3-6 times, and dried in an oven at 50-75°C for 12-24h; in the S5, the product is washed with anhydrous ethanol and water in turn 3-6 times, and dried in an oven at 50-75°C for 12-24h.

8. The method for preparing a Te-modified SnS / biocarbon composite electrode with high SeS2 loading according to claim 1, characterized in that: In S5, the molecular formula of the alkyl tin compound is R n S X 4-n , n=1-4, R is an alkyl group, and X is oxygen, sulfur, chlorine, bromine, iodine or an organic acid.

9. The method for preparing a Te-modified SnS / biocarbon composite electrode with high SeS2 loading according to claim 1, characterized in that: In the S7, the SnS / biocarbon composite material F and Te powder are mixed in an argon atmosphere, and the protective gas for heat treatment is a mixed gas of argon and hydrogen, and the volume ratio of argon to hydrogen is 90-95%:5%-10%.

10. The method for preparing a Te-modified SnS / biocarbon composite electrode with high SeS2 loading according to claim 1, characterized in that: In the S8, the Te-modified SnS / biocarbon composite material G and SeS2 are ground in a glass mortar for 10-30 minutes and then placed in a low-temperature tube furnace. The temperature is raised from room temperature to 170-200°C at a rate of 8-12°C per minute under vacuum conditions, and the reaction is carried out for 12-24 hours to obtain a SeS2-loaded Te-modified SnS / biocarbon composite electrode H.